Triterpenoid saponins fromtheleavesofIlextriflora Bl. - Trịnh, Thị Điệp (2024)
Four triterpenoid saponins were isolated from the leaves of Ilex triflora Bl. collected in Lam Dong Province, Vietnam, using a combination of fractionation and various chromatographic methods. The chemical structures of these compounds were determined by IR, 1H NMR, 13C NMR, DEPT, HMQC, HMBC, COSY, and ESI-MS spectroscopic techniques. The identified compounds were ilekudinoside R, 3-O-α-L-rhamnopyranosyl-(1→2)-α-L-arabinopyranosyl-α-kudinlactone, kudinoside A, and latifoloside A. This is the first time these saponins were isolated from Ilex triflora Bl.